2012
DOI: 10.1371/journal.pone.0032969
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Glutamate Delta-1 Receptor in Mouse Leads to Aberrant Emotional and Social Behaviors

Abstract: The delta family of ionotropic glutamate receptors consists of glutamate δ1 (GluD1) and glutamate δ2 (GluD2) receptors. While the role of GluD2 in the regulation of cerebellar physiology is well understood, the function of GluD1 in the central nervous system remains elusive. We demonstrate for the first time that deletion of GluD1 leads to abnormal emotional and social behaviors. We found that GluD1 knockout mice (GluD1 KO) were hyperactive, manifested lower anxiety-like behavior, depression-like behavior in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 106 publications
(121 reference statements)
11
98
2
1
Order By: Relevance
“…We found a deficit in early developmental processes, including dendritic spine pruning and switch in NMDA receptor subunit in GluD1 KO mice (Gupta et al, 2015). In addition, we previously demonstrated that GluD1 KO exhibits social-interaction and reversal-learning deficits and repetitive behaviors which are core features in several neurodevelopmental disorders, in particular autism spectrum disorders (ASDs) (Yadav et al, 2012(Yadav et al, , 2013Gupta et al, 2015). A recent study demonstrated that neurons derived from induce pluripotent stem cells from Rett syndrome patients exhibit an upregulation of GluD1 (Livide et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…We found a deficit in early developmental processes, including dendritic spine pruning and switch in NMDA receptor subunit in GluD1 KO mice (Gupta et al, 2015). In addition, we previously demonstrated that GluD1 KO exhibits social-interaction and reversal-learning deficits and repetitive behaviors which are core features in several neurodevelopmental disorders, in particular autism spectrum disorders (ASDs) (Yadav et al, 2012(Yadav et al, , 2013Gupta et al, 2015). A recent study demonstrated that neurons derived from induce pluripotent stem cells from Rett syndrome patients exhibit an upregulation of GluD1 (Livide et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…The GluD1 KO mice were obtained from Dr. Jian Zuo (St. Jude Children's Hospital, Memphis, TN) (Gao et al, 2007) and maintained as previously described (Yadav et al, 2012) at a constant temperature (22 6 1°C) and a 12-hour light-dark cycle with free access to food and water. Only male mice were used for these studies.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations